The Impact of Corporate Sector on Social Standards Development in Ukraine - Tretyak, Viktoriia; Kvitka, Anton; Andreieva, Kateryna; Bieliai, Maksym (International Journal of Engineering and Technology, 2018)
This paper is devoted to determining the impact of the corporate sector on the development and implementation of social standards in the society in which it operates. Attention is paid to the formation of trends in social standards changes in terms of the activities of industrial corporations. By studying a number of indicators, a comparative analysis of these processes in Ukraine and Europe is presented. Recommendations for domestic industrial companies have been worked out, implementation of which will significantly improve the competitiveness of Ukrainian corporate sector and determine the tendencies of harmonization of social standards in Ukraine with the European ones.Â Â